Imatinib mesylate treatment in a dog with gastrointestinal stromal tumors with a c-kit mutation - IRIE, Mitsuhiro (J Vet Med Sci, 2015)
A 13-year-old spayed mixed-breed dog was diagnosed with a gastrointestinal stromal tumor (GIST) after histopathological examination of an abdominal mass. Five months after surgical resection of the tumor, we detected the recurrence of GIST with multiple disseminated abdominal lesions. A sequence analysis of cDNA obtained from a biopsy of the recurrent tumors revealed a mutation within exon 9 of the c-kit gene (1523A>T, Asn(508)Ile), which has been shown to cause ligand-independent phosphorylation of the KIT protein in GISTs and canine mast cell tumors (MCTs). Upon detection of the recurrent tumors, we initiated treatment with imatinib mesylate (10 mg/kg, q 24 hr). After 2 months, the dog achieved complete remission. Our findings indicate that canine GIST, and possibly MCT, may be responsive to molecular-targeted therapy.